Synthesis, interface (Au/M2Pc2/p-Si), electrochemical and electrocatalytic properties of novel ball-type phthalocyanines - ÖZKAYA, ALİ RIZA (ROYAL SOC CHEMISTRY, 2012)
The phthalodinitrile derivative (3) was prepared by the reaction of 4,4'-(octahydro-4,7-methano-5H-inden-5- ylidene)bisphenol (1) and 4-nitrophthalonitrile (2) with dry DMF as the solvent in the presence of the base K2CO3 by the method of nucleophilic substitution of an activated nitro group in an aromatic ring. The template reaction of 3 with the corresponding metal salts gave the novel bi-nuclear ball-type metallophthalocyanines, MPcs {M = Co (4), Cu (5), Zn (6)}. Newly synthesized compounds were characterized by elemental analysis, UV-vis, FT-IR (ATR), MALDI-TOF mass and H-1-NMR spectroscopy techniques. The electronic spectra exhibit an intense p -> pi* transition of characteristic Q and B bands of the Pc core. The dielectric properties and interface between the spin coated films of 4-6 and a p-type silicon substrate have been studied by fabricating metal-insulator-semiconductor capacitors. The results indicated that the frequency dependence of the dielectric permittivity, epsilon'(omega), exhibits non-Debye type relaxation for all the temperatures investigated. The ac conductivity results indicated that the conduction mechanism can be explained by a hopping model at low temperatures (<430 K) and a free band conduction mechanism at high temperatures (>= 430 K). The density of interface state calculations on these novel compounds showed that the combination of Au/4/p-Si is a promising structure with a high dielectric constant and a low interface trap density suitable for metal-oxide-semiconductor devices. The electrochemical properties of the Pc complexes were examined by cyclic voltammetry, differential voltammetry and controlled potential coulometry on platinum in non-aqueous media. The complexes showed ring-based and/or metal-based mixed-valence behaviours as a result of the remarkable interaction between the two Pc rings and/or metal centres. The mixed-valence splitting values for the complexes suggested that the mixed valence species are considerably stable. The Vulcan XC-72(VC)/Nafion(Nf)/4 modified glassy carbon electrode showed much a higher catalytic performance towards oxygen reduction than those of VC/Nf/5 and VC/Nf/6 modified ones.
Keywords: GAS-SENSING PROPERTIES; ETHER-SUBSTITUTED PHTHALOCYANINES; OXYGEN REDUCTION; THIN-FILMS; ELECTRICAL-CONDUCTIVITY; ZINC PHTHALOCYANINES; COBALT PHTHALOCYANINES; NICKEL PHTHALOCYANINE; COPPER PHTHALOCYANINE; ACIDIC MEDIUM